2020
DOI: 10.2174/1871520619666191028104339
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin-Fatty Acid Conjugates as Potential ERα/AKT-1 Antagonists for ER Positive Breast Cancer

Abstract: Background: : Current drugs used for the treatment of hormone-dependent breast cancer function as anti-estrogens in the breast, in addition to Estrogen Receptor (ER) agonists in the uterus, thus elevate a woman’s risk of developing uterine cancer. This is due to the lack of selective binding and partial agonistic effect of these drugs towards estrogen receptors. In recent years, therefore, researchers have turned their attention towards antiestrogens devoid of these agonist properties and thus have a mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Because labelled U0126 competes with PD98059 for MEK1 binding, they appear to bind to the same sites on the protein. 62 While it has been demonstrated that U0126 and PD98059 suppress MEK1 phosphorylation and ERK1 and ERK2 activation, these first-generation MEK inhibitors have been extensively used in vivo to identify ERK1 and ERK2 biological activity. Moreover, these two inhibitors have recently been demonstrated to limit ERK5 pathway activation via direct actions on MEK5.…”
Section: Raf Kinases In Cancer: Multifaceted Roles In Tumorigenesis A...mentioning
confidence: 99%
“…Because labelled U0126 competes with PD98059 for MEK1 binding, they appear to bind to the same sites on the protein. 62 While it has been demonstrated that U0126 and PD98059 suppress MEK1 phosphorylation and ERK1 and ERK2 activation, these first-generation MEK inhibitors have been extensively used in vivo to identify ERK1 and ERK2 biological activity. Moreover, these two inhibitors have recently been demonstrated to limit ERK5 pathway activation via direct actions on MEK5.…”
Section: Raf Kinases In Cancer: Multifaceted Roles In Tumorigenesis A...mentioning
confidence: 99%
“…Coumarins are derivatives of 2H-1-benzopyran-2-one, which naturally occurs in plants as free coumarins or their glycoside derivatives (Kashman et al, 1992;Currens et al, 1996;McKee et al, 1998;Creagh et al, 2001;Shokoohinia et al, 2018;Bhatia and Rawal, 2019;Kawai et al, 2019;Li et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). Coumarins have been known for their proapoptotic anticancer activity with inhibitory effects on tumor-promoting signal transduction pathways as well as antiviral activity (Kashman et al, 1992;Currens et al, 1996;McKee et al, 1998;Creagh et al, 2001;Shokoohinia et al, 2018;Bhatia and Rawal, 2019;Kawai et al, 2019;Li et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). The naturally occurring coumarin derivatives, (+)-calanolide A and (-)-calanolide B, have been identified as inhibitors of non-nucleoside HIV-1-specific reverse-transcriptase inhibitory activity (Kashman et al, 1992;Currens et al, 1996;Creagh et al, 2001).…”
Section: Coumarins As a New Class Of Bruton's Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Several semi-synthetic calanolide derivatives have been developed as antiviral drug candidates (Creagh et al, 2001;Sagiv-Barfi et al, 2015;Chen et al, 2016). Researchers have hybridized coumarin moieties with other anticancer pharmacophores as a strategy of developing novel anticancer drugs (Flavin et al, 1996;Bhatia and Rawal, 2019;Kawai et al, 2019;Lin et al, 2019;Makowska et al, 2019;Ramdani et al, 2019;Selvaraj et al, 2019;Wang et al, 2019;Zhang and Xu, 2019). In addition, some natural coumarins such as Psoralidin (Li et al, 2019) and Osthol (Shokoohinia et al, 2018) have been reported to exhibit potent in vitro and in vivo anticancer activity.…”
Section: Coumarins As a New Class Of Bruton's Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estrogen dependency of breast cancer represents a unique feature of the disease that can be manipulated to effectively control growth and/or prevent tumor development. Indeed, the current strategy for treatment of hormone-dependent breast cancer is to block the action of estrogen on tumor cells through either of three possibilities: (a) inhibiting estrogen from binding to its main target ERα using an antiestrogen such as tamoxifen/raloxifen [3][4][5][6][7][8] ; (b) preventing estrogen synthesis using an aromatase inhibitor [9][10][11][12][13][14][15] ; (c) down-regulating ERα protein levels using a pure antiestrogen such as fulvestrant [16][17] .…”
Section: Introductionmentioning
confidence: 99%